Optimalisasi Pelaksanaan Layanan Perpustakaan Untuk Meningkatkan Literasi Siswa - Hidayah, Dian; Widodo; Hasanah, Enung (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to identify and optimize the implementation of library services at SMP Al-Imam Islamic School Balikpapan to enhance student literacy. Currently, the library services play a crucial role in supporting literacy activities, but there is still potential for further development. This research uses a qualitative approach with a case study method, where data were obtained through in-depth interviews, observations, and document analysis. The findings indicate that the library services have shown positive developments, particularly in increasing student participation in literacy programs. The continuously updated book collection and the relevance of literacy programs tailored to students' needs are key factors supporting literacy improvement. Based on these findings, it is recommended to continue innovating library services, such as expanding access to digital resources and developing more interactive and engaging literacy programs. This optimization is expected to further strengthen the role of the library as a literacy center that significantly contributes to improving the quality of education at SMP Al-Imam Islamic School Balikpapan.